Immunological mechanisms in steroid-induced osteonecrosis of the femoral head - Yin, Zhilei; Wu, Longfei; Huang, Jiwei; Zhao, Haiyan (Frontiers in Immunology, 2025)
Steroid-induced osteonecrosis of the femoral head (SONFH) represents a prevalent and complex orthopedic condition, intricately linked to multifaceted dysregulation of the immune system. Prolonged administration of high doses of GCs (GCs) represents a major cause of non-traumatic osteonecrosis of the femoral head (ONFH), with its pathogenesis rooted in the interaction between immune cell dysfunction and imbalances in bone metabolism. This review systematically explores the molecular mechanisms through which GCs induce osteonecrosis via immunological pathways, with emphasis on the impact of macrophage polarization imbalance on the disruption of the bone immune microenvironment. This encompasses the metabolic reprogramming of macrophages and the involvement of critical signaling pathways. This study sought to establish a comprehensive theoretical framework for the immunological regulatory mechanisms underlying SONFH, to provide a detailed understanding of the mechanisms by which GCs induce bone immune disorders, and to offer a robust theoretical foundation for the formulation of early intervention strategies.